Investigation of Grammatical Cohesive Devices Errors Made by Saudi EFL Students in Written Paragraphs: A Case Study of the University of Tabuk, Saudi Arabia - Othman, Ahmed Khider Ahmed (European Scientific Journal, ESJ, 2019)
A good paragraph must be as clear as possible so that the reader can follow sentences, ideas, and details easily. The purpose of this study is to investigate the types, frequencies, and causes of grammatical cohesive devices errors in the written paragraphs which were committed by the Saudi Englishmajor students (male) who are majoring in English language at the Department of Language and Translation at the University of Tabuk in Saudi Arabia. 40 paragraphs were selected randomly from second year first term mid-exams in the year 2018-2019. A mixed design method of both qualitative and quantitative research methodology was used to analyze the participants’ written texts. To analyze the data, a framework by Halliday and Hassan (1976) was adopted. The result of the study showed that the three major types of cohesive devices errors (reference, substitution, and conjunction) were found in the students’ written paragraphs. Hence, they were used in dealing with errors in texts. The most frequently occurred errors were conjunction with the percentage of 52%, reference 37%, and substitution 11%. The findings showed that the Saudi undergraduates committed these kinds of errors due to lack of inadequate grammatical knowledge of these devices, influence of mother tongue interference, lack of vocabulary, and language background. The study recommends that grammatical cohesive devices should be taught explicitly, as well as in association with reading skill, in developing grammatical cohesive devices awareness.